Enhancing multiple benefits of brownfield cleanups by applying ecosystem services concepts - Mastervich, Brooke; Garbach, Kelly; Harwell, Matthew C. (Frontiers in Ecology and Evolution, 2024)
Brownfields are increasingly called upon to be transformed from potentially contaminated, often vacant properties into community assets that provide multiple benefits. Decision-makers are using recent policy tools to encourage brownfields revitalization that helps to combat the climate crisis, apply nature-based solutions, and enhance ecosystem services. Nature-based solutions are actions to protect, sustainably manage, or restore natural or modified ecosystems to address societal challenges, simultaneously providing benefits for people and the environment. Further, bBrownfields revitalization can provide critical opportunities and, particularly, nature-based solutions can enhance multiple ecological, human health, and economic benefits. Through a series of non-exhaustive surveys of existing examples of environmental benefits of cleanups, case study examples of brownfield cleanups achieving environmental benefits, and potential ecosystem services tools relevant to steps of a brownfields cleanup effort, we explore practical ideas for enhancing environmental benefits of brownfields cleanups by applying ecosystem services concepts. Examples of nature-based solutions, where appropriate, include the use of rain gardens, permeable pavements, green spaces, and the use of green technologies. Further, tThis article provides an overview of recent policy initiatives focused on nature-based solutions and enhancing ecosystem services in brownfields cleanup, revitalization, and reuse. Our goals are to increase the knowledge base on these opportunities and discuss how these concepts can be achieved through sharing success stories, accessible outreach materials, and holding workshops to help successfully operationalize these concepts in a community's visioning for upcoming revitalization projects.